ADIPONEKTIN MEREGULASI TURUN EKSPRESI iNOS PADA KULTUR HUVEC’s YANG DIPAPAR LIPO POLYSACCHARIDE (LPS) - Hernani, Yully Endang (Jurnal Kedokteran Brawijaya, 2008)
ABSTRACT Adiponectin  is  a  adipocyte  derivate  protein  involves  in  sensitivity  of  insulin,  anti-inflamation,  and  anti-atherogenic  found  largely  in  plasma.  The  decrease  of  adiponectin  in  the  plasma  is  related  to  obesity, cardiovascular diseases, type II diabetes, hypertension and vascular injuries in nice. In vivo research on strain balb/c mice showed that excessive Adiponectin expression inhibits atherosclerosis with Apo E deficiency. The aim  of  this  research  is  to  find  protective  mechanisms  of  adiponectin  on  vascular  utilizing  in-vitro  Infected HUVEC’s  culture.  There  were  5  groups  :(A)  control  negative  group  or  normal  HUVEC’s,